Utility of post-therapy brain surveillance imaging in the detection of primary central nervous system lymphoma relapse. (February 2017) - Fossard, Gaëlle; Ferlay, Céline; Nicolas-Virelizier, Emmanuelle; Rey, Philippe; Ducray, François; Jouanneau, Emmanuel; Faurie, Pierre; Belhabri, Amine; Sunyack, Marie-Pierre; Chassagne-Clément, Catherine; Thiesse, Philippe; Sebban, Catherine; et al.
Abstract: Background: The optimal follow-up strategy for primary central nervous system lymphoma (PCNSL) patients after first-line therapy is unclear. The goal of this study is to determine the utility of planned brain surveillance imaging in the detection of relapse in a retrospective cohort of PCNSL patients. Methods: Patients were consecutive PCNSL cases treated in Leon Berard Cancer Centre, Lyon, France, from 1985 to 2011. Histology was diffuse large B-cell lymphoma in 94%. Patients were treated by methotrexate (92%) and cytarabine (63%) based-chemotherapy followed by radiotherapy for 108 patients (51%). Clinical records were reviewed for details at relapse and relationship to planned imaging. The imaging follow-up strategy was performed according to each treating physicians. Results: Among 209 PCNSL patients, 127 complete response patients entered in post-treatment observation and 63 (50%) subsequently relapsed. Among the 125 evaluable patients, the majority of relapses (N = 49, 80%) was asymptomatic and identified before the planned brain imaging. Surveillance imaging detected relapses before symptoms in 12 patients who entered in post-therapy observation (10%). The median number of brain imaging during the follow-up was 7 (0–13). A total of 819 MRI/CT-scan were performed leading to the detection of 12 asymptomatic relapses. The one year OS rates were 41% and 58% for symptomatic and non-symptomatic relapses, respectively (P = 0.21). Conclusion: The majority of PCNSL relapses occurred outside planned follow-up with no difference in patient outcome between symptomatic and asymptomatic relapses. The role of brain imaging for the detection of relapses in the follow-up of PCNSL patients remains to be clarified. Highlights: The role of brain imaging for surveillance of primary central nervous system lymphoma is unclear. In our study, 20% of relapses are detected outside planned brain imaging. A total of 819 brain imaging was performed to detect 12 asymptomatic relapses. There was no survival difference after relapse detected clinically or by imaging. These data suggest little utility of routine neuroimaging to detect primary central nervous system lymphoma relapse.